2006
DOI: 10.1007/s10592-005-9075-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of farm fox and hybrid genotypes among wild arctic foxes in Scandinavia

Abstract: In Scandinavia, farmed arctic foxes frequently escape from farms, raising concern about hybridization with the endangered wild population. This study was performed to find a genetic marker to distinguish escaped farm foxes from wild Scandinavian foxes. Microsatellite and mitochondrial control region variation were analyzed in 41 farm foxes. The results were compared with mitochondrial and microsatellite data from the wild population in Scandinavia. The farm foxes were genetically distinct from the wild foxes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Although their origin is quite recent, escaped farm foxes may pose a serious threat to small natural populations through loss of local adaptations and genetic swamping. Hybridization between wild and farmed Arctic foxes was first documented in Iceland (Hersteinsson 1986) and more recently in Scandinavia (Norén et al 2005;Norén, Kvaløy et al 2009). In Iceland, where the Arctic fox population is quite large and robust, there is no known effects of the documented hybridization (Hersteinsson 1986).…”
Section: Genetic Swamping Hybridization and Introgressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although their origin is quite recent, escaped farm foxes may pose a serious threat to small natural populations through loss of local adaptations and genetic swamping. Hybridization between wild and farmed Arctic foxes was first documented in Iceland (Hersteinsson 1986) and more recently in Scandinavia (Norén et al 2005;Norén, Kvaløy et al 2009). In Iceland, where the Arctic fox population is quite large and robust, there is no known effects of the documented hybridization (Hersteinsson 1986).…”
Section: Genetic Swamping Hybridization and Introgressionmentioning
confidence: 99%
“…Farmed foxes are genetically divergent from wild, Scandinavian Arctic foxes (Norén et al 2005). Norén, Kvaløy et al (2009) identified a farm fox specific mitochondrial haplotype (termed H9) in 25 out of 182 samples collected across Scandinavia.…”
Section: Genetic Swamping Hybridization and Introgressionmentioning
confidence: 99%
“…A further potential threat to persistence of Fennoscandian arctic foxes is hybridization between wild and farmed arctic foxes that escape from captivity (Hersteinsson et al, 1989;Linnell et al, 1999;Dal´en et al, 2002;Angerbj¨orn et al, 2004;Andersen et al, 2005;Eide et al, 2005;Nor´en et al, 2005). Commercial production of arctic fox fur was initiated in Alaska at the end of the 19th century.…”
Section: Introductionmentioning
confidence: 99%
“…The arctic fox (Alopex lagopus LINNEAUS) is one example, and frequent escapes are of particular concern in Fennoscandia, Randi (2005) where the native arctic fox population currently consists of approximately 150 adults and is classified as endangered (Norén et al 2005). The situation is similar when it comes to the American mink (Neovison vison SCHREBER): farm-raised mink may escape (or be released) and persist in the wild where American mink are endemic (Kidd et al 2009).…”
Section: Fur Farmsmentioning
confidence: 99%
“…Mating between wild and captive strains of the same species does occur frequently (Kidd et al 2009;Latch et al 2006;Norén et al 2005;Randi 2008), although individuals can sometimes discriminate among them and thus preferentially reproduce with their similes, e.g. in mallard (Cheng et al 1979).…”
Section: Morphologymentioning
confidence: 99%